Felipe Hernández, Peter Kellett and Lea K. Allen (eds.) (2012): Rethinking the Informal City - Graf, Patricia (Critical Reviews on Latin American Research - CROLAR, 2013)
This review discusses the book 'Rethinking the informal City. Critical perspectives from Latin America', edited by  Felipe Hernández, Peter Kellett and Lea K. Allen from a political science perspective considering broader research on formality, informality and city governance in Latin America.